Association between household livestock ownership and childhood stunting in Bangladesh – A spatial analysis - Hossain, Md. Belal; Khan, Jahidur Rahman (Oxford Academic, 2022)
This article was published in The Journal of Tropical Pediatrics [ C The Author(s) [2019]. Published by Oxford University Press. All rights reserved. For permissions, please email: journals.permissions@oup.com] and the definite version is available at: https://doi.org/10.1093/tropej/fmz061. The Journal's website is at: https://academic.oup.com/tropej/article/66/3/248/5570311?login=true